Does early exposure to caffeine promote smoking and alcohol use behavior? A prospective analysis of middle school students. (3rd June 2018) - Kristjansson, Alfgeir L.; Kogan, Steven M.; Mann, Michael J.; Smith, Megan L.; Juliano, Laura M.; Lilly, Christa L.; James, Jack E.
Abstract: Background and Aims: Despite the negative consequences associated with caffeine use among children and youth, its use is increasingly widespread among middle school students. Cross‐sectional studies reveal links between caffeine and other substance use. The potential for caffeine use to confer increased vulnerability to substance use, however, has not been investigated using prospective designs. We hypothesized that caffeine use at baseline would be associated positively with increased alcohol use, drunkenness, smoking and e‐cigarette use. Design: Prospective cohort study with 12 months separating baseline from follow‐up. Setting: West Virginia, USA. Participants: Middle school students (6th and 7th grades; n = 3932) in three West Virginia (WV) counties provided data at baseline and follow‐up 12 months later. Measurements: Youth self‐reported their use of caffeine from multiple sources (e.g. soda, energy drinks, coffee and tea), cigarette smoking, electronic cigarette use, alcohol use and drunkenness. Findings: Cross‐lagged path models for individual substance use categories provided a good fit to the data. Controlling for demographic variables and other substance use at baseline, caffeine at time 1 (T1) was associated positively with T2 cigarette smoking (β = 0.27, P = 0.001), e‐cigarette use (β = 0.21, P = 0.001), alcohol use (β = 0.17, P = 0.001) and drunkenness (β = 0.15, P = 0.001). Conversely, non‐significant relations emerged between three of four substances at T1 and caffeine at T2. Positive relations were found between e‐cigarette use at T1 and caffeine use at T2 (β = 0.07, P = 0.006). These findings were supported by an omnibus model with all substances included. Specifically, significant relations were observed between caffeine at T1 and all substance use outcomes at T2, whereas no significant relations were observed between substance use and caffeine over time. Conclusions: Caffeine may promote early use of other types of substances among middle school‐aged adolescents.